Web Based Used Motorcycle Sales Information System Design at Wipa Motor Using Laravel Framework - Kemal Haerul Abror; Umar Mansyuri; Rahadian Arief (Brilliance: Research of Artificial Intelligence, 2025)
This research seeks to build and develop a web-based information system for the sale of used motorcycle at Wipa Motor, a motorcycle dealer that focuses on selling used motorcycles. The problems faced are limited customer access to used motorcycle information and inefficiencies in recording transactions that are done manually. This limited access causes customers to only visit dealers or contact dealers via WhatsApp to obtain information related to used motorcycles. Meanwhile, manual transaction recording has the potential to increase the risk of errors and data loss in sales reporting. The method used in this study is the waterfall method, which includes needs analysis, system design, implementation, and testing. The data was collected through interviews with Wipa Motor owners. This research aims to develop a web-based information system that facilitates real-time access to used motorbike information and enables online transactions for costumers. This system was built using the laravel framework to automate the recording of sales transactions and the management of motorcycle stock which was previously done manually. The results show that this system is expected to improve operational efficiency, speed up the transaction process, and expand market reach. In addition, the system can improve sales data management by generating more accurate reports. In conclusion, the implementation of this web-based system can increase the effectiveness of Wipa Motor's operations, provide convenience for customers, and strengthen Wipa Motor's image as a modern dealer and adaptable to technological developments.